Patterns and Themes in Canadian Picture Books Published in 2017: A Content Analysis of 132 Titles Using Dresang’s Lens of Radical Change - Brenna, Beverley; Khan, Irteqa; Morstad, Miranda (Alberta Journal of Educational Research, 2020)
This comprehensive examination of 132 picture books originally published by Canadian publishers in 2017, and written and/or illustrated by at least one creator living in Canada, offers qualitative and quantitative findings that demonstrate patterns and themes in relation to number of titles, authors, illustrators, characters, genres, audiences, and readability characteristics, while addressing particular elements of Dresang’s (1999) notion of Radical Change. Books were identified from multiple sources with results compared to a previous study (Author 3), demonstrating a marginal increase of titles since 2015 where 120 books were identified, and a continued increase from 2005 where 57 books were identified. Of particular note in the current sample were the 13 books created by Indigenous authors and/or illustrators and presenting Canadian Indigenous content and perspectives, calculated at 9.8 % of the study sample, compared to previous results where books by Indigenous authors and/or illustrators comprised 3.5 % of the sample in 2005 and 10% in 2015. These findings, and other patterns, themes and possible trends, are suggested as underpinnings for future research involving further changes in the field of Canadian children’s literature in education as well as further research into reader response regarding contemporary titles. While this paper does address aspects of diversity present in this study sample, a second article disseminates detailed findings related to representations of ethnicity. .